Study on the irradiation effect towards water filtration element - Abu Bakar A.A.; Pauzi A.M.; Mujaini M.; Mohamed A.A.; Idris F.M. (Institute of Physics Publishing, 2023)
Atoms; Failure (mechanical); Grain size and shape; Irradiation; Neutrons; Radiation; Water filtration; Filtering elements; Irradiation effect; Material compositions; Mechanical damages; Neutron and gamma irradiation; Neutron fluences; Physical effects; Strong correlation; Neutron irradiation; Atoms; Correlation; Filtration; Neutrons; Paper; Water